The Effect of Online Learning Using Schoology on Student Learning Outcomes in Momentum and Impulse Matter - Syafriyanti, Aulia (Asian Journal of Science Education, 2022)
This study intends to ascertain the impact of Schoology-based online instruction on students' learning outcomes in momentum and impulse matter. A non-equivalent pretest-posttest control group design using a quasi-experimental methodology was adopted. All of the second-semester students in X class Science MAN 1 Medan make up the study's population. Purposive sampling was utilized to choose the study's sample. The test utilized consists of 20 questions with multiple choices about momentum and impulse matter, all of which have been validated by the validator. According to the findings, the control class's pre-test average value is 50.67, whereas the experiment class is 51.83 on average. The two classes' data are found to have equally distributed normal and homogeneous distributions in the tests for normality and homogeneity. The findings revealed that using Schoology for online learning had a significant impact on student learning outcomes in physics subjects.